Ccnp 4 - Inc., Cisco Systems; Lewis, Wayne ([S.l.] : Cisco Press, 2004)
The only authorized textbook for the Cisco Networking Academy Program CCNP 4: Network Troubleshooting Companion Guide contains all the information from the online curriculum. With this Companion Guide, you have access to the course information anytime, anywhere, plus the following reference, study, and review tools: Chapter Objectives indicate key concepts for focused study. Highlighted key terms throughout the chapter where they are used in context. A comprehensive glossary provides key term definitions to serve as a study aid. "Check Your Understanding" review questions, presented at the end of each chapter, act as a review and study guide. They reinforce the concepts introduced in the chapter and help test your understanding before you move on to a new chapter. The answers to the questions are provided in an appendix. Lab activities from the CCNP 4: Network Troubleshooting Lab Companion are referenced throughout the book. Completing these labs gives you hands-on experience so that you can apply theory to practice. This Cisco authorized textbook is a portable desk reference designed to complement the CCNP 4: Network Troubleshooting course in the Cisco Networking Academy Program. The topics covered include documentation, baselining, troubleshooting tools, troubleshooting methodologies, and per-OSI-layer troubleshooting techniques. Use this Companion Guide to help prepare for the Cisco Internetwork Troubleshooting exam (642-831), which is one of the four required exams to obtain the CCNP certification. Companion Title: CCNP 4: Network Troubleshooting Lab Companion ISBN: 1-58713-142-0 Companion CD-ROM The CD-ROM contains a test bank with 200 practice exam questions exclusive to Cisco Press covering topics for the CCNP CIT 642-831 exam. The test engine is powered by Boson Software, Inc., a Cisco Learning Partner. www.boson.com This book is part of the Cisco Networking Academy Program Series from Cisco Press. The products in this series support and complement the Cisco Networking Academy Program.
Keywords: Debugging in computer science; Computer networks; Maintenance and repair; Computer networks Management; Computer networks